PENERAPAN PEMBELAJARAN IPS BAGI SISWA SMP BERBASIS PENGENALAN KEARIFAN LOKAL BALIMAU KASAI MELALUI TEKNIK HUMANISTTIK - Aisyah Nur Hanifah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Based on humanistic learning theory, learning objectives through local wisdom are based on the introduction of Balimau Kasai, which functions to humanize a human being. Learning activities are considered successful when students understand their environment and themselves. Students in the learning process must try to gradually be able to achieve self-actualization well. The development of learning based on the introduction of local wisdom to junior high school students can be an effective solution to increasing student interest in Social Sciences (IPS) lessons. Moreover, the concept of learning based on the introduction of localistic traditions and culture can trigger the emergence of a spirit of nationalism and patriotism in students to always respect the diversity of cultures and traditions around them. An example of local wisdom in Indonesia that can be introduced to students as teaching material for daily life is the Balimau Kasai tradition originating from Kampar Regency, Riau Province. Silberman (2006) states that local wisdom is a value system that is reflected in the life behavior of local people to be able to interact with the environment in which they live wisely and wisely. So, it can provide awareness to students to remain loyal to the existence of local culture and traditions that exist in everyday life.